Komunikasi Instruksional Lembaga Kursus dan Pelatihan Pelawi Salon dalam Pemberdayaan Masyarakat di Kota Binjai - Alwan Galib; Muhammad Husni Ritonga (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
The Vocational Skills Education (PKK) program at course and training institutions holds a significant role in advancing skills and fostering economic independence within the community. The success of this program is substantially shaped by the effectiveness of instructional communication applied in the learning process between instructors and students. This study aims to analyze the effectiveness and quality of instructional communication at Pelawi Salon Course and Training Institution in the Vocational Skills Education program in the field of bridal makeup as a community empowerment effort in Binjai City. A qualitative approach with a descriptive method was employed. Data were collected through in-depth interviews, field observations, and documentation, and subsequently analyzed through data reduction, data presentation, and conclusion drawing to obtain a comprehensive understanding of the instructional communication process. The findings reveal that instructional communication throughout the training process was conducted interactively through the application of demonstration methods and direct practice, enabling students to grasp the material in an applied manner. Two-way interaction between instructors and participants further encouraged a participatory learning process. In addition, the availability of training facilities and evaluation through practical examinations linked to the Competency Test Center contributed to the advancement of participants' skills. This study concludes that the training program contributes to strengthening students' competencies and expanding employment and entrepreneurial opportunities in the bridal makeup sector, thereby supporting the attainment of community empowerment objectives